Pengaruh proses fermentasi kacang merah (phaseolus vulgaris l.) menggunakan ragi tempe (rhizopus sp.) dan enzim papain terhadap kualitas sosis kacang merah - Siti Mutmainah; Ana Ummu Mas’ula; Septiani Budi Ariska; Lailatul Masruroh; Hapsari Titi Palupi (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Red beans (Phaseolus vulgaris L.) is a commodity beans are very popular, and are abundant in Indonesia. The purpose of this study to determine the effect of different fermentation methods on quality sausage red beans and determine the best fermentation method on the sausage red beans based on the analysis and organoleptic clams. The method used in this study is RAK one single factor consisting of four treatments. F1 (red bean fermentation using yeast tempeh (Rhizopus oligosporus)), F2 (fermented using enzymes papain), F3 (red bean fermentation using yeast tempeh (Rhizopus oligosporus) + enzyme papain) and F4 (without red bean fermentation process). The observations were analyzed using statistical ANOVA (Analysis of Variance) followed by Tukey test sensory testing is carried out by Friedman test. The best treatment method de Garmo effectiveness index. The results showed Effect of treatment fermentation methods which differ significantly affect chemical parameters include moisture content, ash content, protein content, fat content rude, crude fiber content and carbohydrate content and the nature organolepti color, aroma, flavor, and texture of the sausage beans. best fermentation method in the manufacture of sausages red beans based on a chemical that is F4 (without red bean fermentation process) with a value of 9.29% moisture content, ash content of 4.41%, 12.47% protein content, fat content rough 0.51% , crude fiber content of 3.71%, and the carbohydrate content of 73.3%. While the treatment is the best value organoleptic F1 (red bean fermentation using yeast tempeh (Rhizopus oligosporus)) Color 8 (really like), the scent 7.48 (like), flavor 6.6 (a bit like), and the texture of 7.92 (very like).